2012
DOI: 10.1007/s11427-012-4302-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of seed germination in Orobanche spp. by extracts of traditional Chinese medicinal herbs

Abstract: The co-evolution of Orobanche spp. and their hosts within the same environment has resulted in a high degree of adaptation and effective parasitism whereby the host releases parasite germination stimulants, which are likely to be unstable in the soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Previously, it was reported that Arabidopsis thaliana can differentially stimulate germination in numerous weed seeds [7] which strongly supports our findings. Furthermore, in a study, extracts from Chinese medicinal herbs have been shown to differentially stimulate seed germination in numerous Orobanche species [24] which is in agreement to our work. Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27].…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously, it was reported that Arabidopsis thaliana can differentially stimulate germination in numerous weed seeds [7] which strongly supports our findings. Furthermore, in a study, extracts from Chinese medicinal herbs have been shown to differentially stimulate seed germination in numerous Orobanche species [24] which is in agreement to our work. Current findings support the reported allelopathic influence of rice on the seed germination of sunflower broomrape and clover broomrape [27].…”
Section: The Differential Germination Indicates a Genetic And Biochemsupporting
confidence: 91%
“…Successful germination induction in the sunflower broomrape indicates that the crops used in rotation excrete certain chemical compounds that actively stimulate its germination. Previously, extracts from Chinese medicinal herbs have been reported to induce seed germination in numerous Orobanche species such as O. minor, O. cumana, and P. aegyptiaca [24], supporting our results that plant biochemicals induce germination of sunflower broomrape. Therefore, our findings lay the foundation for a research direction to identify bioactive compounds from wheat, pepper, and sugar beets using advanced technological protocols such as mass spectrophotometry.…”
Section: Differential Response Of Broomrape Species Indicates the Allsupporting
confidence: 90%
“…Selection and breeding of varieties with a high germination-inducing activity to O. minor would be possible in wheat and cotton. The screening of more than 600 Chinese medicinal herb species for an investigation of their germination-inducing activities to O. cumana, O. minor and P. aegyptiaca indicated that the methanolic extracts of many Chinese herbal species effectively stimulate seed germination of the parasites [137].…”
Section: Trap Crop and Catch Cropmentioning
confidence: 99%
“…Different plant species have been reported to show a strong ability to stimulate seed germination of different Orobanche species by more than 90%, and extracts of hundreds of plant species were tested for possibly stimulating or inhibiting seed germination of different Orobanche spp. ; many proved effective and may be considered as trap, cover, and catch species or a source of natural germination stimulants for these parasites [104][105][106].…”
Section: Germination Stimulantsmentioning
confidence: 99%